Study on Minimum Contention Window Size Adjustment Algorithm Based on Neighbor Nodes Number Estimation in Vehicular Ad Hoc Network - Dapeng Li; Tao Yuan; Haitao Zhao (Dianxin kexue)
In order to solve the periodic broadcast scalability of IEEE 802.11p-based VANET on control channel, a minimum contention window adjustment algorithm based on neighbor nodes number estimation was proposed. First of all, in order to minimize the collision probability, the relationship between minimum contention window（CWmin）and active node number n was deduced on the basis of Markov model IEEE 802.11 broadcast backoff. Then minimum contention window was adjusted dynamically by estimating the number of neighbor nodes in real time. Finally, the proposed algorithm and the original's fixed CWmin method were compared by simulation, and the results show that the proposed algorithm is superior to the original method in broadcast reception rate.